Cellulose and vanadium plasmonic sensor to measure Ni2+ ions - Sheh Omar, Nur Alia; Yap, Wing Fen; Ramli, Irmawati; Mohd Azmi, Umi Zulaikha; Hashim, Hazwani Suhaila; Abdullah, Jaafar; Mahdi, Mohd Adzir (Multidisciplinary Digital Publishing Institute, 2021)
A novel vanadium–cellulose composite thin film-based on angular interrogation surface plasmon resonance (SPR) sensor for ppb-level detection of Ni(II) ion was developed. Experimental results show that the sensor has a linear response to the Ni(II) ion concentrations in the range of 2–50 ppb with a determination coefficient (R2) of 0.9910. This SPR sensor can attain a maximum sensitivity (0.068° ppb−1), binding affinity constant (1.819 × 106 M−1), detection accuracy (0.3034 degree−1), and signal-to-noise-ratio (0.0276) for Ni(II) ion detection. The optical properties of thin-film targeting Ni(II) ions in different concentrations were obtained by fitting the SPR reflectance curves using the WinSpall program. All in all, the proposed Au/MPA/V–CNCs–CTA thin-film-based surface plasmon resonance sensor exhibits better sensing performance than the previous film-based sensor and demonstrates a wide and promising technology candidate for environmental monitoring applications in the future.